Implementation of Fluorescent-Protein-Based Quantification Analysis in L-Form Bacteria - Di Tian; Yiyuan Liu; Yueyue Zhang; Yunfei Liu; Yang Xia; Boying Xu; Jian Xu; Tetsuya Yomo (Bioengineering, 2024)
Cell-wall-less (L-form) bacteria exhibit morphological complexity and heterogeneity, complicating quantitative analysis of them under internal and external stimuli. Stable and efficient labeling is needed for the fluorescence-based quantitative cell analysis of L-forms during growth and proliferation. Here, we evaluated the expression of multiple fluorescent proteins (FPs) under different promoters in the Bacillus subtilis L-form strain LR2 using confocal microscopy and imaging flow cytometry. Among others, Pylb-derived NBP3510 showed a superior performance for inducing several FPs including EGFP and mKO2 in both the wild-type and L-form strains. Moreover, NBP3510 was also active in Escherichia coli and its L-form strain NC-7. Employing these established FP-labeled strains, we demonstrated distinct morphologies in the L-form bacteria in a quantitative manner. Given cell-wall-deficient bacteria are considered protocell and synthetic cell models, the generated cell lines in our work could be valuable for L-form-based research.